APLIKASI PEMBELAJARAN MOBILE BAHASA PORTUGIS DALAM BAHASA TETUM UNTUK MEMBANTU MASYARAKAT TIMOR-LESTE DALAM PENGUASAAN BAHASA PORTUGIS SEBAGAI BAHASA NASIONAL - Adina Sarmento Nunes; Erfanti Fatkhiyah; Suraya - (Jurnal SCRIPT, 2018)
Being able to speak Portuguese properly is an obligation for people of East Timor since Portuguese is their national language. For that reason, some efforts are needed to facilitate that need. One thing that can be done is providing an application that can become a practical learning resource, by using the technology development on mobile device so that the resource can be accessed by people, whenever and wherever they are. This study is aimed to help people of East Timor in learning Portuguese, by presenting a mobile-based application which is run on android platform. The application is created by using Mobile Application Development Lifecycle (MADLC) approach. Generally, the study is conducted in three stages, they are defining requirements, designing user interface and testing the application. Application is created on Android Studio IDE, version 2.1.1 and can be run on android device with minimum level of API 14. Application uses Firebase Cloud Database as its database platform. The results of the study is a prototype of android application of Portuguese learning in Tetum language, called “Portun”. The testing is conducted within the IDE with help from Junit which is built-in plugin in Android Studio. The testing results show that the prototype is well-functioned so that itcan be developed more in the future, by they who concern to facilitate the people of East Timor in accessing resource of Portuguese easily.